2023
DOI: 10.2147/copd.s400985
|View full text |Cite
|
Sign up to set email alerts
|

Plasma miR-150-5p as a Biomarker for Chronic Obstructive Pulmonary Disease

Abstract: Purpose To investigate the potential of plasma microRNA-150-5p (miR-150-5p) as a biomarker for chronic obstructive pulmonary disease (COPD) and its relationship with clinical indicators such as pulmonary function. Patients and Methods Fifty-nine patients with COPD and twenty-six healthy control individuals were recruited in the Second People’s Hospital of Hefei from September 2021 to September 2022. The plasma expression level of miR-150-5p was measured by quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…of COPD Patients Age Sex (Male/Female) No. of Control Age Sex (Male/Female) Sample Type Test Method Normalizer Chen et al 17 2019 China English 104 SCOPD: 67.53±8.49, AECOPD: 65.13±9.87 88/16 50 63.47±11.31 41/9 Plasma qRT-PCR U6 Ding et al 18 2023 China English 59 75.12 ± 7.85 50/9 26 71.65 ± 6.35 20/6 Plasma qRT-PCR Cel-miR-39-3p Gao et al 19 2022 China Chinese 164 SCOPD: 67.97±8.24, AECOPD: 69.12±7.89 107/57 82 68.27±8.22 57 /25 Plasma qRT-PCR U6 Geng et al 20 2020 China English 53 60.32± 6.35 32/21 50 59.83±5.29 25/25 Serum qRT-PCR U6 Jiang et al …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of COPD Patients Age Sex (Male/Female) No. of Control Age Sex (Male/Female) Sample Type Test Method Normalizer Chen et al 17 2019 China English 104 SCOPD: 67.53±8.49, AECOPD: 65.13±9.87 88/16 50 63.47±11.31 41/9 Plasma qRT-PCR U6 Ding et al 18 2023 China English 59 75.12 ± 7.85 50/9 26 71.65 ± 6.35 20/6 Plasma qRT-PCR Cel-miR-39-3p Gao et al 19 2022 China Chinese 164 SCOPD: 67.97±8.24, AECOPD: 69.12±7.89 107/57 82 68.27±8.22 57 /25 Plasma qRT-PCR U6 Geng et al 20 2020 China English 53 60.32± 6.35 32/21 50 59.83±5.29 25/25 Serum qRT-PCR U6 Jiang et al …”
Section: Resultsmentioning
confidence: 99%
“…These criteria involved excluding reviews, in vitro and in vivo experiments, as well as articles with sample sources other than blood or those with unusable data. In conclusion, a total of 16 eligible studies [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] were incorporated into the meta-analysis, comprising 8 English-language publications and 8 Chinese-language publications. The publication period of the included studies spans from 2013 to 2023.…”
Section: Literature Searchmentioning
confidence: 99%
“…At this time, as an initial precaution, we quantified the samples using the Spectrophotometer (Thermo Scientific™ NanoDrop™) to evaluate the purification of the extracted RNA. Regarding endogenous control and duplicate reactions, we did not find standardization in the literature, including studies published in recent years using a single endogenous miRNA for control ( Sekovanić et al, 2021 ; Bayati et al, 2022 ; Couto et al, 2022 ; Li et al, 2022 ; Ding et al, 2023 ; Higashi et al, 2023 ). Furthermore, Couto et al (2022) cite duplicate reactions and the other authors do not cite the number of reactions carried out.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ouyang et al found that miR-185-5p and miR-182-5p were involved in the development of COPD and might serve as potential biomarkers for the diagnosis of COPD [ 7 ]. Ding et al also found that miR-150-5p could be used for the diagnosis and disease assessment of COPD [ 8 ]. The expression levels of miR-203a-3p and miR-375 were significantly higher in both COPD patients and healthy people with smoking [ 9 ].…”
Section: Introductionmentioning
confidence: 99%